In Vitro Thermal Requirements of Some Beauveria sp. Isolates Under Constant Conditions - Cristina Fătu, Ana; Maria Lumînare, Cristina; Nicolae Cojanu, Daniel; Monica Dinu, Mihaela; Maria Andrei, Ana (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
The thermal tolerance of four isolates of Beauveria bassiana and one isolate of Beauveria pseudobassiana was evaluated in vitro, by measuring the colonial diameters, on PDA medium, at temperatures between 5 and 35 ° C, during 14 days. The data obtained were used to calculate the growth rate of fungal colonies (mm / day), using linear regression. The representation of the values corresponding to the minimum, optimal and maximum temperature for vegetative growth was a curve described by a modified beta (ß) mathematical function. The minimum growth temperature of these isolates varied between 3.4 and 4.5 °C, the optimum temperature varied between 21.8 and 22.9 °C, except for one isolate of which optimal temperature was 26.8 °C, while the maximum temperature was varied for all isolates between 35.0 and 35.7 °C.